Nematodes Recent Advances, Management and New Perspectives - Edu Kaspary, Tiago (IntechOpen, 2022)
Nematodes are microscopic, eel-like roundworms that can infect humans, animals, and plants and cause serious damage and yield losses in a wide range of crops worldwide. This book includes thirteen chapters that address such topics as diagnosing nematode infections in crops (fruits and horticultural crops), management and biological control of plant-parasitic nematodes, biological indicators of nematodes, and entomopathogenic and marine nematodes. This comprehensive volume is a useful resource for students, teachers, researchers, field workers, and all those interested in and working with nematodes.